Cervical Schwannoma of Sympathetic Chain: A Rare Case Report - Zulkifli, Muhd Faiz Bin; Kenali, Solahudin Mohd (Central Asian Journal of Medical Sciences, 2018)
Objectives: It is very rare to find nerve sheath tumors that originate from the sympathetic chain. Imaging play important role to help surgeon to make a diagnosis. In this case, computed tomography (CT) scan used to establish the pre-operative diagnosis. Methods: This can be demonstrated through a case of a 52-year-old man presented with a swelling on the right side of his neck for 2 years. CT scan show a mass lying behind the right internal jugular vein and deep to the sternomastoid. Result: The patient was successfully treated by surgery and has not shown evidence of recurrence. Histopathology examination (HPE) confirmed the diagnosis of schwannoma. Conclusion: Diagnostic imaging gives essential pre-operative information which is useful to plan optimal surgical procedure. Complete surgical excision should carry out and biopsy must be performed for histology examination to confirm the diagnosis.